Association Between Insulin-like Growth Factor-1 rs35767 Polymorphism and Type 2 Diabetes Mellitus Susceptibility: A Meta-Analysis - Zeng, Qiaoli; Zou, Dehua; Zeng, Qiaodi; Chen, Xiaoming; Wei, Yue; Guo, Runmin (Frontiers in Genetics, 2021)
Background : Insulin-like growth factor-1 (IGF-1) has been demonstrated to increase fatty acid β oxidation during fasting, and play an important role in regulating lipid metabolism and type 2 diabetes mellitus (T2DM). The rs35767 (T>C) polymorphism, a functional SNP was found in IGF-1 promoter, which may directly affect IGF-1 expression. However, the inconsistent findings showed on the IGF-1 rs35767 polymorphism and T2DM risk. Methods: We performed a comprehensive meta-analysis to estimate the association between the IGF-1 rs35767 and T2DM risk among four genetic models (the allele, additive , recessive and dominant models). Results: A total 49587 T2DM cases and 97906 NDM controls were included in the allele model, a total 2256 T2DM cases and 2228 NDM controls were included in the other three genetic models ( the additive; recessive and dominant models). In overall analysis, the IGF-1 rs35767 was shown to be significantly associated with increased T2DM risk for the allele model (T vs. C: OR = 1.251, 95% CI: 1.082–1.447, P = 0.002) , additive model ( homozygote comparisons: TT vs. CC: OR = 2.433, 95% CI: 1.095–5.405, P = 0.029; heterozygote comparisons: TC vs. CC: OR = 1.623, 95% CI: 1.055–2.495, P = 0.027) and dominant model (TT+CT vs. CC: OR = 1.934, 95% CI: 1.148–3.257, P = 0.013) with random effects model. After omitting Gouda’s study could reduce the heterogeneity, especially in the recessive model (TT vs. CC+CT: I2= 38.7%, P=0.163 ), the fixed effects model for recessive effect of the T allele (TT vs. CC+CT) produce results that were of borderline statistical significance (OR = 1.206, 95% CI: 1.004–1.448, P = 0.045). And increasing the risk of T2DM in Uyghur population of subgroup for the allele model. Conclusions: The initial analyses that included all studies showed statistically significant associations between the rs35767 SNP and type 2 diabetes, but after removing the Gouda et al. study produced results that were mostly not statistically significant. Therefore, there is not enough evidence from the results of the meta-analysis to indicate that the rs35767 SNP has a statistically significant association with type 2 diabetes.